Sosialisasi Satuan Tugas Pencegahan dan Penanaganan Tindakan Kekerasan dan Sex di Lingkungan Perguruan Tinggi - Ludifika Claudia Owa; Maria Nadila Wea; Katarina Ndekung; Gerda Mariana Kimun; Maria Susanty Moi (Universitas Maritim AMNI Semarang, 2025)
Sexual violence in higher education institutions is a serious issue that has physical, psychological, and social impacts. This study aims to enhance the understanding of students at STKIP Citra Bakti about the prevention and handling of sexual violence through socialization using the Participatory Action Research (PAR) method. This activity involved 40 first-semester students from the PGPAUD study program, including discussions, case studies, and evaluations. The results show an increased awareness among students about the definition, prevention, and reporting procedures of sexual violence, as well as the importance of implementing the values of Pancasila in creating a safe campus environment. It is recommended to continue this socialization activity periodically and strengthen campus policies related to the handling of sexual violence